"An Almost Undiscovered Country": Frank Leslie's 1890 Alaska Expedition and the Tradition of Gilded Age Adventure Journalism. Issue 1 (1st April 2016) - Cronin, Mary M.
Abstract : In the spring of 1890, W.J. Arkell, editor of Frank Leslie's Illustrated Newspaper, sent a team of reporters (accompanied by scouts and native guides) to Alaska to explore the nation's newest territory. The journalists were instructed to write "graphic narratives" of their adventures and produce illustrations "of the strange sights they met" for the readers back home. The often-richly illustrated articles, which were serialized during 1890 and 1891, provide an excellent opportunity to study a phenomenon of the late 1800s: Gilded Age adventure journalism. The reporters constructed uneven narratives that blended first-person adventure journalism, naturalist and ethnographic observations, historical information, and political commentary, while also elaborating on Alaska's resources. The reporters embraced many commonly held stereotypes of the American West and its inhabitants, while their accounts promoted territorial expansion in the cause of Manifest Destiny. This research argues that Alaska's "newness" as a territory coupled with its vast spaces and resources led the journalists to construct narratives that included views more commonly expressed in the first half of the century: that Alaska, as a frontier location, was a wild and savage place, a territory that could and should be tamed by individuals of Anglo and European stock for the betterment of the American nation.